Current control of grid-connected inverter using integral sliding mode control and resonant compensation - Seung-Jin Yoon; Thanh Van Nguyen; Kyeong-Hwa Kim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
To eliminate the adverse effect from parameter variations as well as distorted grid conditions, a current control scheme of an LCL-filtered grid-connected inverter using a discrete integral sliding mode control (ISMC) and resonant compensation is presented. The proposed scheme is constructed based on the cascaded multiloop structure, in which three control loops are composed of grid-side current control, capacitor voltage control, and inverter-side current control. An active damping to suppress the resonance caused by LCL filter can be effectively realized by means of the inverter-side feedback control loop. Furthermore, the seamless transfer operation between the grid-connected mode and islanded mode is achieved by the capacitor voltage control loop. To retain a high tracking performance and robustness of the ISMC as well as an excellent harmonic compensation capability of the resonant control (RC) scheme at the same time, two control methods are combined in the proposed current controller. As a result, the proposed scheme yields a high quality of the injected grid currents and fast dynamic response even under distorted grid conditions. Furthermore, to reduce the number of sensors, a discrete-time reduced-order state observer is introduced. Simulation and experimental results are presented to demonstrate the effectiveness of the proposed scheme.